2008
DOI: 10.1590/s0037-86822008000400014
|View full text |Cite
|
Sign up to set email alerts
|

Candidemia em hospital terciário do nordeste do Brasil

Abstract: A freqüência de infecções hematogênicas por Candida (candidemia) tem aumentado consideravelmente, especialmente em unidades de terapia intensiva e ou de assistência a pacientes críticos 2 3 4 7 8 14 15 17 20 24 . O aumento na freqüência de candidemia tem sido observado particularmente entre pacientes em uso de antibióticos, terapia imunossupressora, nutrição parenteral, e em pacientes expostos a múltiplos procedimentos invasivos 11 24 .Espécies do gênero Candida, em particular Candida albicans, têm emergido co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
1
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 22 publications
7
15
1
13
Order By: Relevance
“…However, Chang et al 19 reported a prevalence of C. albicans of 45.8% among analyzed candidemia infections at the University Hospital of the State of Mato Grosso do Sul. In Brazil and in our study, several studies have indicated C. tropicalis as the second most frequent isolate in cases of candidemia among hospitalized patients 12,20,24 . C. tropicalis is the fourth most frequent Candida species isolated in cases of candidemia in the United States 30 and the third most frequent isolate in Spain 8 and Asia 6 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, Chang et al 19 reported a prevalence of C. albicans of 45.8% among analyzed candidemia infections at the University Hospital of the State of Mato Grosso do Sul. In Brazil and in our study, several studies have indicated C. tropicalis as the second most frequent isolate in cases of candidemia among hospitalized patients 12,20,24 . C. tropicalis is the fourth most frequent Candida species isolated in cases of candidemia in the United States 30 and the third most frequent isolate in Spain 8 and Asia 6 .…”
Section: Discussionsupporting
confidence: 64%
“…These results are similar to other recent studies conducted in central-western Brazil. Yamamoto et al 20 reported a prevalence of C. albicans of 39% among isolates in Cuiabá, State of Mato Grosso, and other reports from the same country have indicated a predominance of NCAC species over C. albicans in clinical samples isolated from hospitalized patients 12,24 .…”
Section: Discussionmentioning
confidence: 96%
“…(14)(15)(16)(17)(18) Such results are similar to those found in this study, in which contamination with Candida parapsilosis following the cleaning/disinfection process persisted in three hospital mattresses.…”
Section: Discussionsupporting
confidence: 88%
“…1 A expansão do número de pacientes críticos tem determinado o aparecimento de novas espécies de Candida. 2 Entre as infecções invasivas causadas pelo gê-nero Candida, vale salientar a relevância clínica dos casos de infecção de corrente sanguínea, complica-ção esta conhecida como candidemia ou candidíase hematogênica.…”
Section: Introductionunclassified
“…3 Infecções hematogênicas por Candida spp também podem ser adquiridas por via exógena, através do contato das mãos de profissionais de saúde, com pacientes portadores de catéteres vasculares em posição central, implante de próteses contaminadas, bem como pela administração parenteral de soluções contaminadas. 1 A capacidade dos fungos de causar doenças invasivas é muito bem documentada: as espécies de Candida constituem, hoje, o quarto micro-organismo mais isolado nas hemoculturas de pacientes internados nos Estado Unidos, 4 sendo este responsável por cerca de 80% das infecções fúngicas no ambiente hospitalar, constituindo causa relevante das infecções de corrente sanguínea, respondendo por cerca de 8% dos casos das infecções documentadas neste sítio. 3 A hemocultura representa um importante mé-todo laboratorial de diagnóstico das fungemias.…”
Section: Introductionunclassified